Comparison of Two Isolation Methods for Naturally Preserved DNA in Ambergris - Fathurahman, Fabian Rizky; Suman, Ali; Mahmoud, Hanan Hassan Alsheikh; Nuryanto, Agus (Biosaintifika: Journal of Biology & Biology Education, 2025)
DNA extraction is a fundamental initial step in numerous molecular research studies. Different extraction methods are required for different biological samples to obtain high-quality DNA. Therefore, this step is one of the limiting factors for the success of molecular analysis. There has been no research evaluating an appropriate method to extract DNA from ambergris jetsam samples. This study aims to determine an appropriate method for extracting DNA from whale ambergris samples. The ambergris sample was collected from the southern coast of Cilacap. DNA extraction was performed using a commercial DNA isolation kit and the Chelex® 100 method. The extracted DNA was visualized using agarose gel electrophoresis followed by quantification with a UV Nanodrop spectrophotometer. The data were analyzed descriptively to determine the most effective extraction method. The success of the extraction was also assessed by measuring the DNA concentration using the Nanodrop spectrophotometer. The results showed that the commercial isolation kit failed to produce genomic DNA from whale ambergris, as indicated by the absence of stained DNA bands on the agarose gel. In contrast, the Chelex® 100 method successfully produced genomic DNA from ambergris, as evidenced by the presence of stained DNA bands on the agarose gel and a high quantity of genomic DNA after a Nanodrop measurement. It can be concluded that the Chelex® 100 method is more suitable than commercial kits for extracting DNA from ambergris samples. This finding contributes to the development of various scientific fields based on molecular data by providing evidence that each biological sample requires an appropriate method to obtain high-quality DNA.